Kualitas Fisik, Kimia dan Mikrobiologi Susu Kambing pada Waktu Pemerahan yang Berbeda di Peternakan Cangkurawok, Balumbang Jaya, Bogor (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The aim of this study was to determine the physical, chemistry, and microbiological quality of goat’s milk collected from morning and afternoon milking. A total of 3 of crossbred goat (PE) milk were used in this study. These samples were analyzed for total plate count (TPC), Staphylococcus sp, Escherichia coli, and Salmonella sp. Test anova shown any significant differences ( p